Strategie tekstowe apologetyki chrześcijańskiej (Tertulian, "Apologetyk" 16) - Jakielaszek, Jarosław (Vox Patrum, 2007)
The paper examines a group of subjunctive clauses attested in Tertullian’s works, which seem to deviate from the rules of consecutio temporum. Earlier researchers assumed that the unusual pattern follows from brachylogy, otherwise frequent in Tertullian’s writings. It is argued that in fact such clauses obey the rules of the Classical period and there is no need to explain their behavior as resulting from a brachylogical expression.